ANALISIS KEBIJAKAN PERUBAHAN HARGA BBM (BAHAN BAKAR MINYAK) TERHADAP PENDAPATAN MASYARAKAT PERTANIAN DI DESA PLOSOGENUK KECAMATAN PERAK KABUPATEN JOMBANG - Munawaroh, Siti (JPEKBM (Jurnal Pendidikan Ekonomi, Kewirausahaan, Bisnis dan Manajemen), 2023)
This study aims to determine the policy of changing the price of fuel oil (BBM) on people's income in Plosogenuk village, Perak District, Jombang Regency. This study uses a qualitative approach by conducting 2 (two) studies, namely : Observational research and interview research. Research by conducting observations observing changes in fuel princes in Plosogeuk village, and research conducting interviews by conducting direct conversations with people in Plosogenuk Vullage regarding the income of agricultural communities from rising fuel prices (BBM). With the interview research, there were 5 (five) respondents who worked as farmesrs in Plosogenuk Village and 2 (two) respondents who worked as farm laborers. The results of this study show that changes in fuel prices (BBM) have an impact on income on community income in Plosozenuk village, Perak district, Jombang Regency, as the community's average rent for agricultural equipment is, thus the effect of changes in fuel prices (BBM) on the income of people in Plosozenuk village, Perak district, Jombang Regency.